CRISPR/dCas9 for hepatic fibrosis therapy: implications and challenges - Nianan Luo; Wenjun Zhong; Jiangbin Li; Jianguo Lu; Rui Dong (Molecular Biology Reports, 2022)

B-YOLOX-S: A Lightweight Method for Underwater Object Detection Based on Data Augmentation and Multiscale Feature Fusion - Jun Wang; Shuman Qi; Chao Wang; Jin Luo; Xin Wen; Rui Cao (Journal of Marine Science and Engineering, 2022)
With the increasing maturity of underwater agents-related technologies, underwater object recognition algorithms based on underwater robots have become a current hotspot for academic and applied research. However, the existing underwater imaging conditions are poor, the images are blurry, and the underwater robot visual jitter and other factors lead to lower recognition precision and inaccurate positioning in underwater target detection. A YOLOX-based underwater object detection model, B-YOLOX-S, is proposed to detect marine organisms such as echinus, holothurians, starfish, and scallops. First, Poisson fusion is used for data amplification at the input to balance the number of detected targets. Then, wavelet transform is used to perform Style Transfer on the enhanced images to achieve image restoration. The clarity of the images and detection targets is further increased and the generalization of the model is enhanced. Second, a combination of BIFPN-S and FPN is proposed to fuse the effective feature layer obtained by the Backbone layer to enhance the detection precision and accelerate model detection. Finally, the localization loss function of the prediction layer in the network is replaced by EIoU_Loss to heighten the localization precision in detection. Experimental results comparing the B-YOLOX-S algorithm model with mainstream algorithms such as FasterRCNN, YOLOV3, YOLOV4, YOLOV5, and YOLOX on the URPC2020 dataset show that the detection precision and detection speed of the algorithm model have obvious advantages over other algorithm networks. The average detection accuracy mAP value is 82.69%, which is 5.05% higher than the benchmark model (YOLOX-s), and the recall rate is 8.03% higher. Thus, the validity of the algorithmic model proposed in this paper is demonstrated.

Insight into enhanced degradation of tetracycline over peroxymonosulfate activated via biochar-based nanocomposite: performance and mechanism - Tiehong Song; Yanjiao Gao; Jian Ye; Xin Zhang; Rui Su; Jiacheng Luo (Environmental Science and Pollution Research, 2022)

Abscisic acid activates desiccation tolerance responses in intertidal seaweed Neoporphyra haitanensis - Caixia Zhang; Juanjuan Chen; Rui Yang; Qijun Luo; Tiegan Wang; Peng Zhang; Haimin Chen (Frontiers in Marine Science, 2022)
Intertidal macroalgae have adapted to deal with environmental stresses, in particular desiccation. The phytohormone abscisic acid (ABA) plays an important role in the regulation of a suite of critical responses in plants, including desiccation tolerance. The red alga Neoporphyra haitanensis contains a high level of ABA, but its mechanism of action in N. haitanensis is unknown. In this study, the effect of ABA treatment on the relative water content of thalli during the dehydration-rehydration cycle was evaluated and it was identified that ABA treatment resulted in decreased thalli water loss and an accelerated rehydration process. The effects of addition of ABA upon the activation of antioxidant responses, photosynthetic parameters and gene transcription profiles of N. haitanensis were also evaluated. The results revealed that exogenous ABA regulated the activation of the antioxidant system, including by increasing the activity of antioxidant enzymes, increasing the concentrations of ascorbic acid (AsA) and glutathione (GSH), as well as upregulating the expression of genes encoding antioxidant enzymes and enzymes that synthesize AsA and GSH. ABA treatment also inhibited photosynthesis by reducing light capture and down-regulating the Calvin cycle to save energy; ABA supplementation further simultaneously activated repair mechanisms to avoid excessive DNA and protein damage. The results presented herein demonstrate that ABA plays a crucial role in the regulation of stress tolerance in seaweeds, which may be of great importance when examining the adaptation of this organism to the intertidal environment.

U-net Models Based on Computed Tomography Perfusion Predict Tissue Outcome in Patients with Different Reperfusion Patterns - Yaode He; Zhongyu Luo; Ying Zhou; Rui Xue; Jiaping Li; Haitao Hu; Shenqiang Yan; Zhicai Chen; Jianan Wang; Min Lou (Translational Stroke Research, 2022)

Heavy metal pollution status and deposition history of mangrove sediments in Zhanjiang Bay, China - Daobin Tang; Songying Luo; Suyan Deng; Rui Huang; Bishan Chen; Ziyi Deng (Frontiers in Marine Science, 2022)
Mangroves have high ecological service value and play an important role in achieving carbon neutrality. However, the ecological services provided by mangroves are gradually declining due to the threat of various pollutants, especially heavy metal (HM) pollution. Researching the status and history of heavy metals (HMs) in mangrove sediments improves understanding of how mangroves can be protected. We studied the Zhanjiang Bay mangroves, which is an important part of the Zhanjiang Mangrove National Nature Reserve, and is greatly affected by human activities, as an example. We analyzed the pollution levels and deposition process of HMs and their influencing factors. In the mangrove surface sediments of Zhanjiang Bay, Pb, Cr, and Co were slightly to moderate enriched and Cu was moderate-heavy enriched. Zn and Hg showed moderate-heavy enrichment and heavy enrichment, respectively. Cu, Zn, Hg, and Co were 1.5, 1.88, 2.66, and 1.27 times the local background, respectively. Cu, Zn, and Hg mainly originated from anthropogenic sources, and Co may have derived from natural sources. The HM data of mangrove sedimentary cores in Zhanjiang Bay were obtained for the first time; high HM content appeared in the deep layer of the cores but not in the mangrove surface sediments. Both cores were well documented for the effects of natural and anthropogenic factors on the deposition process of HMs. Among them, the high enrichment of Hg in 1909–1921 may be closely related to human activities rather than natural formation. Before 1954, dense mangroves favored the accumulation and gradual increase of HMs. The intense human activity in 1945–1963 during the period of economic construction and reclamation of the Nansan Island Engineering led to significant increases in Cu, Zn, Pb, Cr, and Co, which reached their highest values in more than one hundred years. After 1963, anthropic factors such as deforestation and conversion to aquaculture sharply reduced mangrove area. Reclamation engineering enhanced tidal erosion. Natural factors such as precipitation, storm surge, sea-level rise, and high tides have accelerated the erosion and dilution of mangrove sediments in Zhanjiang Bay. These factors have led to the gradual reduction of HM content in sedimentary cores.

Sustained ocular delivery of desmopressin acetate via thermoreversible in situ gel formulation: preparation and in vitro/in vivo evaluation - Fang Lei; Huimin Zhang; Rui Luo; Qingsong Fei; Luyu Bai; Ning He (Journal of Pharmaceutical Investigation, 2022)

Combined Effects of Eco-Substrate and Carbon Addition on Water Quality, Fish Performance and Nutrient Budgets in the Pond Polyculture System - Kun Guo; Zhigang Zhao; Jun Xie; Liang Luo; Shihui Wang; Rui Zhang; Wei Xu; Xiaoli Huang (Fishes, 2022)
Traditional aquaculture can cause serious environmental pollution. Biofilm and biofloc technology have the potential to limit aquaculture pollution. An outdoor experiment was conducted to evaluate the combined effects of eco-substrates and carbon addition on water quality, fish performance and nutrient budgets in the pond polyculture system. In the treatment group, the total ammonia nitrogen, nitrate nitrogen, nitrite nitrogen, and total nitrogen of the water were significantly lower compared to the control group (p 92%) and P (>95%) input during the experiment. Comprehensive accumulation was the main N (>58%) and P (>69%) output. The N and P feed input and comprehensive accumulation output declined in the treatment group. The N utilization efficiency in the experimental group increased slightly (p > 0.05), while the P utilization efficiency in the experimental group was significantly higher compared to the control (p

Effects of Alkalinity on the Antioxidant Capacity, Nonspecific Immune Response and Tissue Structure of Chinese Mitten Crab Eriocheir sinensis - Mingshuai Li; Shihui Wang; Zhigang Zhao; Liang Luo; Rui Zhang; Kun Guo; Lanlan Zhang; Yuhong Yang (Fishes, 2022)
The effects of various levels of alkalinity stress (0, 18.25, 35.41, 52.53 and 69.74 mmol/L) in Chinese mitten crab (Eriocheir sinensis) were investigated by means of measuring hepatopancreas antioxidant system and serum nonspecific immune system-related indices at 0, 12, 24, 48 and 96 h, hepatopancreas tissue structure at 96 h. The activities of superoxide dismutase (SOD), catalase (CAT), glutathione (GSH) and aspartate aminotransferase (AST) in each concentration group generally showed a trend of a first increasing and then decreasing during the 96-h stress process (p 0.05). The activities of CAT, GSH and AST in all treatment reached peak values at 24–48 h. At 96 h of alkalinity stress, the activities of GSH, alanine aminotransferase (ALT), acid phosphatise (ACP) and alkaline phosphatise (AKP) in the 18.25 mmol/L group were not significantly different with the control group (p > 0.05). The activities of SOD and CAT in the 52.53 and 69.74 mmol/L treatment were significantly lower than those in the control group (p

Plant-mediated rhizospheric interactions in rice and water spinach intercropping enhance Si uptake by rice - Chuanchuan Ning; Lei Wang; Rui Liu; Taowen Pan; Yixia Cai; Jihui Tian; Shiming Luo; Kunzheng Cai (Plant and Soil, 2022)

Population Genetic Diversity and Differentiation of Mitten Crab, Genus Eriocheir, Based on Microsatellite Markers - Shihui Wang; Liang Luo; Rui Zhang; Kun Guo; Wei Xu; Zhigang Zhao (Fishes, 2022)
Mitten crab, Eriocheir sensu stricto, is an important indigenous aquatic species and food source in Eastern Asia. Genetic diversity is an important prerequisite for the conservation and utilization of germplasm resources. However, the genetic diversity and differentiation of Eriocheir s. s. remains unclear. This study evaluated population genetic diversity and genetic differentiation of three Eriocheir s. s. populations from Suifenhe (SFH), Liaohe (LH), and Nanliujiang (NLJ), China, based on 19 microsatellite markers. The mean observed number of alleles (Na) was 22.84 alleles, and the mean polymorphism information content (PIC) was 0.86, which demonstrated high genetic diversity. The allele frequency distribution showed an “L” shape, ranging from 0.01 to 0.74. The genetic diversity parameter values of the LH population were higher than those of the other two populations. All pairwise FST values showed significant differences among the three Eriocheir s. s. populations (p

Development of Solid-State Anaerobic Digestion and Aerobic Composting Hybrid Processes for Organic Solid Waste Treatment and Resource Recovery: a Review - Chuanren Qi; Rongrong Yin; Xingzu Gao; Jie Chen; Rui Wang; Zhicheng Xu; Wenhai Luo; Guoxue Li; Yangyang Li (Current Pollution Reports, 2022)

Evaluating the stability of Outang landslide in the Three Gorges Reservoir area considering the mechanical behavior with large deformation of the slip zone - Junbiao Yan; Zongxing Zou; Rui Mu; Xinli Hu; Jincheng Zhang; Wen Zhang; Aijun Su; Jinge Wang; Tao Luo (Natural Hazards, 2022)

Thermal crosslinking synthesis of ethylene–vinyl acetate copolymer supported floating TiO2 photocatalyst: characterization and photocatalytic performance - Qiang Wu; Jizhong Meng; Hang Yao; Rui Tang; Shoujun Yuan; Yulan Wang; Wei Wang; Haiping Luo; Zhen-Hu Hu (Environmental Science and Pollution Research, 2022)

A study on the infection status and transmission of avian leukosis virus subgroup J in Hy-line brown roosters - Fanfeng Meng; Qiuchen Li; Rui Han; Guanlong Xu; Xintao Gao; Fubing Luo; Guangnian Shen; Xiaodong Liu; Zhifang Zhang; Peng Zhao; Guozhong Zhang (Archives of Virology, 2022)

Bone Marrow-Derived Alk1 Mutant Endothelial Cells and Clonally Expanded Somatic Alk1 Mutant Endothelial Cells Contribute to the Development of Brain Arteriovenous Malformations in Mice - Sonali S. Shaligram; Rui Zhang; Wan Zhu; Li Ma; Man Luo; Qiang Li; Miriam Weiss; Thomas Arnold; Nicolas Santander; Rich Liang; Leandro do Prado; Chaoliang Tang; et al. (Translational Stroke Research, 2022)

Combination Effects of Polyphenols Present in Sugarcane on Proliferation in MCF-7 Human Breast Cancer Cells - Yujiao Yang; Rui Zheng; Pingling Zhang; Jing Wen; Yue Luo; Zhengang Zhao; Lijun You; Chi-Tang Ho (Sugar Tech, 2022)

Chlorogenic acid, a natural product as potential inhibitor of COVID-19: virtual screening experiment based on network pharmacology and molecular docking - Wen-Xiang Wang; Ying-Rui Zhang; Shi-Ying Luo; Yun-Sen Zhang; Yi Zhang; Ce Tang (Natural Product Research, 2022)

Targeting iNOS Alleviates Early Brain Injury After Experimental Subarachnoid Hemorrhage via Promoting Ferroptosis of M1 Microglia and Reducing Neuroinflammation - Wenhao Qu; Ying Cheng; Wei Peng; Yan Wu; Tongyu Rui; Chengliang Luo; Jian Zhang (Molecular Neurobiology, 2022)

The level of endogenous JA is critical for activation of SA- and JA-defensive signaling pathway in japonica rice cultivar Ziyu44 upon Magnaporthe oryzae infection - Xingyu An; Hui Zhang; Jinlu Li; Rui Yang; Qianchun Zeng; Mo Wang; Qiong Luo (Journal of Plant Pathology, 2022)

Impact and trade off analysis of land use change on spatial pattern of ecosystem services in Chishui River Basin - Rui Luo; Shiliang Yang; Zhiying Wang; Tianming Zhang; Pengqun Gao (Environmental Science and Pollution Research, 2022)

Dysfunction of FadA‐cAMP signalling decreases Aspergillus flavus resistance to antimicrobial natural preservative Perillaldehyde and AFB1 biosynthesis - Kunlong Yang; Qingru Geng; Yue Luo; Rui Xie; Tongzheng Sun; Zhen Wang; Ling Qin; Wei Zhao; Man Liu; Yongxin Li; Jun Tian (Environmental Microbiology, 2022)
Summary Aspergillus flavus is an opportunistic fungal pathogen that colonizes agriculture crops with aflatoxin contamination. We found that Perillaldehyde (PAE) effectively inhibited A . flavus viability and aflatoxin production by inducing excess reactive oxygen species (ROS). Transcriptome analysis indicated that the Gα protein FadA was significantly induced by PAE. Functional characterization of FadA showed it is important for asexual development and aflatoxin biosynthesis by regulation of cAMP‐PKA signalling. The Δ fadA mutant was more sensitive to PAE, while Δ pdeL and Δ pdeH mutants can tolerate excess PAE compared to wild‐type A . flavus . Further RNA‐sequence analysis showed that fadA was important for expression of genes involved in oxidation–reduction and cellular metabolism. The flow cytometry and fluorescence microscopy demonstrated that Δ fadA accumulated more concentration of ROS in cells, and the transcriptome data indicated that genes involved in ROS scavenging were downregulated in Δ fadA mutant. We further found that FadA participated in regulating response to extracellular environmental stresses by increasing phosphorylation levels of MAPK Kinase Slt2 and Hog1. Overall, our results indicated that FadA signalling engages in mycotoxin production and A . flavus resistance to antimicrobial PAE, which provide valuable information for controlling this fungus and AF biosynthesis in pre‐ and postharvest of agricultural crops.

Investigation on the Lift Force Induced by the Interceptor and Its Affecting Factors: Experimental Study with Captive Model - Rui Deng; Zezhen Zhang; Fuqiang Luo; Pengnan Sun; Tiecheng Wu (Journal of Marine Science and Engineering, 2022)
An interceptor is an appendage widely used for high-speed planing boats to reduce resistance and modify hull attitude by the lift force-induced, but the relationship between the induced lift force and the factors affecting it are still not clear, especially for the vessels other than the planing hull. In this paper, a model test of a series of models is performed to investigate the lift force induced by an interceptor and the influence of the affecting factors systematically. The lift forces induced by the interceptor are tested in the conditions of different velocities, interceptor heights, angles, and drafts in the towing tank. The effects of each factor and the coupled effects are analyzed. It is found by the experimental results that the lift coefficient of the induce lift force in the present investigation is approximately proportional to the square of the non-dimensional velocity and interceptor height, but the effect of the interceptor height is of a limited extent. The influence of angle and draft on the lift force induced by the interceptor cannot be ignored in the present study. The induced lift force is decreased when the angle of the plate is reduced and is enhanced when the draft is increased.

Evaluation of suitable qRT-PCR normalization genes for various citrus rootstocks - Wen He; Rui Xie; Huan Li; Yan Wang; Qing Chen; Yuanxiu Lin; Yunting Zhang; Ya Luo; Yong Zhang; Haoru Tang; Xiaorong Wang (Plant Biotechnology Reports, 2022)

A feasible vibration measurement and active control method of reinforced concrete lightweight pier railway bridges for heavy-haul monorail trains - Ling-kun Chen; Li-zhong Jiang; Rui Li; Qiao Li; Ming Zhang; Nan Zhang; Jin-zhang Luo; Liang Ling; Sheng-yang Zhu (European Journal of Environmental and Civil Engineering, 2022)

Serine protease HtrA2/Omi regulates adaptive mitochondrial reprogramming in the brain cortex after ischemia/reperfusion injury via UCP2-SIRT3-PGC1 axis - Hao Meng; Lian-Kun Sun; Jing Su; Wan-Yu Yan; Yao Jin; Xin Luo; Xian-Rui Jiang; Hong-Lei Wang (Human Cell, 2022)

Variations in bacterial and archaeal community structure and diversity along the soil profiles of a peatland in Southwest China - Wei Li; Mingmo Luo; Rui Shi; Defeng Feng; Zhenan Yang; Huai Chen; Bin Hu (Environmental Science and Pollution Research, 2022)

The specialized mitotic behavior of human embryonic stem cells - Rui Lyu; Xuemei Wu; Nan Ma; Difei Wang; Shuang Sun; Youguang Luo; Jun Zhou; Xinyi Lu; Min Liu; Dengwen Li (Cell and Tissue Research, 2022)